Revisionist narratives: locating six Black artist-teachers onto the map of twentieth-century modern art in Zimbabwe - Muvhuti, Tichapera Barnabas (Rhodes University, Faculty of Humanities, Department of Fine Art)
Job Kekana (1916-1995) was a South African sculptor and teacher who moved to Zimbabwe in 1944, where he founded the Kekana School of Art and Craft in the early 1960s. There were also a few Black Zimbabwean artist-teachers, namely, Sam Songo (1929-1977), Cornelius Manguma (b. 1935), Lazarus Khumalo (1930-2015), Joram Mariga (1927-2000) John Hlatywayo (b. 1928), who were either working with missionaries Canon Edward Paterson (1895-1974) and Father John Groeber (1903-1973) at the Cyrene and Serima workshops respectively and later on at the Mzilikazi Arts and Crafts Centre, or with Frank McEwen (1907- 1994) at the National Gallery school. This thesis examines the relative invisibility of Kekana and the selected Black artist-teachers in the dominant discourse of the history and development of modern art in Zimbabwe. Employing the biographical approach as a methodology, and modernism as an analytical tool and foregrounding African thinkers like Chika Okeke-Agulu Elizabeth Georgis, Emma Wolukau- Wanambwa and Salah Hassan, this research exposes the possible reasons for their exclusion from the canon, which are rooted in a gatekeeping culture shown by actors in the local art scene, including art historians and scholars, as well as cultural workers in institutions like the National Gallery of Zimbabwe who have not sufficiently questioned and possibly shaken the enshrined legacies of Paterson, Groeber and McEwen. Canons mostly tend to tell a story that privileges and excludes others from the art narrative of a nation. With the arrival of Frank McEwen on the scene in the late 1950s the stone sculpture tradition rose to prominence in such a way that it overshadowed other forms of art produced in the two mission schools or workshops at Serima and Cyrene. In the process, Kekana and his students at the Kekana School of Art and Craft were relegated to the peripheries of the canon as they carved in wood and tended to work in a more representational style. While there is literature acknowledging the role of the missionaries in laying the foundation of modern art in Zimbabwe, local artists-cum-teachers working with them are only recognised as a footnote on the nation's map of modern art. Recognising that canons are always evolving and shifting, and without discrediting the work of the three mentioned expatriates "“ and to an extent that of Tom Blomefield of the Tengenenge Workshop "“ this thesis attempts to expand the canon by arguing for the inclusion of the critiqued overlooked six. Citing the efforts of researchers, scholars and curators in multicultural South Africa to bring the previously marginalised generation of Black modernists into the mainstream, this thesis demonstrates that it is possible to spotlight the narratives of the Black artists and teachers who continue to occupy peripheral space in the history of Zimbabwe. This comparative analysis is done bearing in mind the temptation of falling into the trap of glorifying 'South African exceptionalism'. In analysing the Black artist-teachers' contributions as a counter-narrative, this research proposes a more heterogeneous modernism and revisionist art history.
Keywords: Modernism (Art) -- Zimbabwe; Art, Modern; Wood-carving; Stone carving; Art, African; Artists as teachers; Art schools -- Zimbabwe